Disconnection in Information Exchange During Pediatric Trauma Transfers: A Qualitative Study - Hadley S Sauers-Ford MPH, CCRP (SAGE Publishing, 2021)
Pediatric patients experiencing an emergency department (ED) visit for a traumatic injury often transfer from the referring ED to a pediatric trauma center. This qualitative study sought to evaluate the experience of information exchange during pediatric trauma visits to referring EDs from the perspectives of parents and referring and accepting clinicians through semi-structured interviews. Twenty-five interviews were conducted (10 parents and 15 clinicians) and analyzed through qualitative thematic analysis. A 4-person team collaboratively identified codes, wrote memos, developed major themes, and discussed theoretical concepts. Three interdependent themes emerged: (1) Parents’ and clinicians’ distinct experiences result in a disconnect of information exchange needs; (2) systems factors inhibit effective information exchange and amplify the disconnect; and (3) situational context disrupts the flow of information contributing to the disconnect. Individual-, situational-, and systems-level factors contribute to disconnects in the information exchanged between parents and clinicians. Understanding how these factors’ influence information disconnect may offer avenues for improving patient–clinician communication in trauma transfers.